2002
DOI: 10.1034/j.1600-0404.2002.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes in patients with clinically active multiple sclerosis

Abstract: The increased concentration of LTB4 in the CSF of MS patients may indicate a biological importance for this mediator in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…As discussed above (see section II.D), the beneficial effects on EAE after either genetic or pharmacological BLT 1 R targeting (Fretland et al, 1991;Gladue et al, 1996;Kihara et al, 2010) suggest that that BLT 1 R signaling may potentially affect both the onset and severity of MS. In support of this, increased levels of LTB 4 have been detected in cerebrospinal fluid from patients with MS (Neu et al, 1992(Neu et al, , 2002. Of interest, 5-LO was identified as one of the most up-regulated genes by microarray analysis in both human MS lesions and in brains from mice after EAE induction (Whitney et al, 2001).…”
Section: F Potential Therapeutic Applicationsmentioning
confidence: 82%
“…As discussed above (see section II.D), the beneficial effects on EAE after either genetic or pharmacological BLT 1 R targeting (Fretland et al, 1991;Gladue et al, 1996;Kihara et al, 2010) suggest that that BLT 1 R signaling may potentially affect both the onset and severity of MS. In support of this, increased levels of LTB 4 have been detected in cerebrospinal fluid from patients with MS (Neu et al, 1992(Neu et al, , 2002. Of interest, 5-LO was identified as one of the most up-regulated genes by microarray analysis in both human MS lesions and in brains from mice after EAE induction (Whitney et al, 2001).…”
Section: F Potential Therapeutic Applicationsmentioning
confidence: 82%
“…There have been contradictory reports regarding the change of leukotriene levels in MS patients and animal models. Some studies found that the LTB4 and LTC4 levels are significantly increased in the cerebrospinal fluid (CSF) of MS patients compared with the controls [117,118]. But no significant difference exists in LTC4 production between MS and control peripheral blood monocytes and macrophages [118,119].…”
Section: Leukotriene Receptorsmentioning
confidence: 99%
“…The 5-LOX gene was found to be a top risk gene in EAE (24). The brain concentrations of 5-LOX products, LTB 4 and LTD 4 , were upregulated (18,(22)(23), and favored the migration of inflammatory cells and lymphocytes in the brain of EAE mice (36)(37)(38). In the cuprizone model, the brain expression of 5-LOX was highly increased (39).…”
Section: Arachidonic Acid Pathway Activation In Animal Models Of Multmentioning
confidence: 99%